2020
DOI: 10.1002/jpen.1830
|View full text |Cite
|
Sign up to set email alerts
|

Role of Ultrasonography in Estimating Muscle Mass in Sarcopenic Obesity

Abstract: Background: Sarcopenic obesity (SO) is the coexistence of sarcopenia and obesity in an individual. The present study is designed to define the usefulness of skeletal muscle ultrasonography (US) in the definition of SO. Methods: Eighty-nine participants aged ≥65 whose body mass index (BMI, kg/m 2) was ≥30 were consecutively enrolled in an outpatient clinic of geriatric medicine. All underwent comprehensive geriatric assessment. US measurements were obtained in 6 different muscles consisting of core and limb mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 34 publications
1
22
0
1
Order By: Relevance
“…8 These elements, which are needed for a proper interpretation of the ICCs, have commonly been missing in general medical literature. Table 1 summarizes the elements reported in the five papers published in the Journal of Parenteral and Enteral Nutrition [1][2][3][4][5] regarding a particular topic, the reliability of muscle mass measurements by different methods. Note that only one study reported, in the methods and/or results, all necessary elements for a proper interpretation of the ICCs or a strategy for choosing.…”
Section: Intraclass Correlation Coefficient and Reliability Of Muscle Mass Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…8 These elements, which are needed for a proper interpretation of the ICCs, have commonly been missing in general medical literature. Table 1 summarizes the elements reported in the five papers published in the Journal of Parenteral and Enteral Nutrition [1][2][3][4][5] regarding a particular topic, the reliability of muscle mass measurements by different methods. Note that only one study reported, in the methods and/or results, all necessary elements for a proper interpretation of the ICCs or a strategy for choosing.…”
Section: Intraclass Correlation Coefficient and Reliability Of Muscle Mass Measurementsmentioning
confidence: 99%
“…In the last year, five papers that reported intraclass correlation coefficients (ICCs) for the reliability of muscle mass measurements were published in the Journal of Parenteral and Enteral Nutrition. [1][2][3][4][5] the degree of correlation and agreement between different measurements and is subject to a variety of statistical assumptions, violations of which may lead to inflated estimates. 6 Based on three different models (one-way random effects, two-way random effects, and two-way mixed effects), two types of measurements (single or average measures), and two output definitions (consistency or absolute agreement), there are, by convention, 10 types of ICCs 7 differentially used for various purposes, such as repeatability and reliability.…”
Section: E T T E R T O T H E E D I T O R Intraclass Correlation Coefficient and Reliability Of Muscle Mass Measurementsmentioning
confidence: 99%
“…Unregulated fluid retention in those severe endocrinological impairments may suffer from exacerbations of concomitant heart disease associated with sarcopenic obesity and low testosterone, such as the cases of heart failure discussed earlier due to increased peripheral resistance from volume overload [96,97]. From a clinical perspective, aromatized TRT leading to potential estradiol conversion and fluid retention may also impact stratification of sarcopenic obesity as studies using different imaging modalities for evaluation of body composition implicate edema as a erroneously non-adipose mass, which may lead to differential assessments of true sarcopenic obesity magnitude by healthcare providers [98,99]. The latter may impact treatment guidelines, graded nutritional counseling, and exercise plans based on an altered perception of phenotype relative to physiological status.…”
Section: Oxandrolone Sarcopenic Obesity and Cardiovascular Healthmentioning
confidence: 99%
“…We thank Kara et al for their response to our article, which we read with great interest 1 . We respectfully disagree with their initial comment that sarcopenia is a regional condition rather than a total fat‐mass condition, as all recent definitions consider sarcopenia as a generalized loss of skeletal muscle mass 2 .…”
mentioning
confidence: 93%